AIP Conference Proceedings 2009
DOI: 10.1063/1.3137720
|View full text |Cite
|
Sign up to set email alerts
|

On the Global Occurrence and Impacts of Transient Luminous Events (TLEs)

Abstract: Based on the first four years of the ISUAL (Imager of Sprites and Upper Atmospheric Lightning) experiment onboard the FORMOSA!-2 sateUite, ELVEs are found to be the most abundant type (-80%) of TLEs (transient luminous events), whereas sprites and halos only combine to account for -20%. The distribution of sprites and halos closely resemble that of the cloud-to-ground lightning. However, nearly 60% of ELVEs occurred over the ocean, a feature indicating that the high peak current lightning is more abundant over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
28
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 20 publications
(30 citation statements)
references
References 25 publications
(36 reference statements)
2
28
0
Order By: Relevance
“…Besides ISUAL mission (2004-) (Chern et al, 2003;Mende et al, 2005;Su et al, 2005;Hsu et al, 2009) (Garipov et al, 2005;Garipov et al, 2006;Shneider & Milikh, 2010). With the Tatiana-1 data, Shneider and Milikh (2010) studied the atmospheric electricity phenomena that can serve as sources for short millisecond range flashes; they reported that the UV flashes in the millisecond scale detected by Tatiana-1 may have been generated by gigantic blue jets (GBJ).…”
Section: Other Present Orbital Missions Of Tlesmentioning
confidence: 99%
See 2 more Smart Citations
“…Besides ISUAL mission (2004-) (Chern et al, 2003;Mende et al, 2005;Su et al, 2005;Hsu et al, 2009) (Garipov et al, 2005;Garipov et al, 2006;Shneider & Milikh, 2010). With the Tatiana-1 data, Shneider and Milikh (2010) studied the atmospheric electricity phenomena that can serve as sources for short millisecond range flashes; they reported that the UV flashes in the millisecond scale detected by Tatiana-1 may have been generated by gigantic blue jets (GBJ).…”
Section: Other Present Orbital Missions Of Tlesmentioning
confidence: 99%
“…Kuo et al (2008) analyzed the photometric and the imagery brightness of TLEs (sprites, halos and elves), and found that total energy deposition rate of TLEs is ~1 GJ/min in the middle atmosphere. Hsu et al (2009) re-examed a more complete set of ISUAL recorded TLEs, and discovered that the global TLE occurrence rates should be 72, 3.7, and ~1 events/minute, respectively, for elvess, halos, and sprites. Comparing with the results from the first three years of the ISUAL experiment reported in Chen et al (2008), the global occurrence rates for elves and halos are higher due to the adoption of different correction factors.…”
Section: The First Satellite Mission For the Survey Of Tles: Isualmentioning
confidence: 99%
See 1 more Smart Citation
“…From the first four years (July 2004 -June 2008) of the ISUAL survey on the FORMOSAT-2 satellite, elves are found to be the most abundant type (~80%) of TLEs, whereas sprites and halos only combine to account for ~20%, defying the impression gained from the ground TLE observation Hsu et al 2009). …”
Section: The Tle Global Distribution and Occurrence Ratesmentioning
confidence: 99%
“…Hence the free electron content for the mesosphere over the Caribbean region at most can be elevated by ~10% Hsu et al 2009). …”
Section: Charge Impact Of Elves To the Mesospheric Electron Densitymentioning
confidence: 99%